Feature Writing Training for Increasing the Capacity of the Pulo Geulis Tourism Community Bogor - Setiawati, Titin; Corliana, Tellys (Institut Teknologi dan Bisnis Asia Malang, 2024)
Purpose: This research paper aims to address the untapped tourism potential in RW 04 Pulo Geulis, Bogor City. It highlights the significance of empowering residents with feature writing skills to create compelling publications about the village's unique harmony of tolerance, ultimately boosting tourism and improving the local economy. Method: The study employs a Community Service Program (PKM) to provide feature writing training to the Pulo Geulis Tourism Community. It utilizes qualitative methods to assess participants' writing skills and gauge the impact of the training on their ability to produce quality publications. Practical Applications: The findings of this research have practical implications for both the tourism industry and community development efforts. By equipping residents with feature writing skills, the program enhances their capacity to promote Pulo Geulis as a tourist destination, attracting more visitors and stimulating economic growth in the area. Conclusion: This study underscores the importance of harnessing local resources and empowering communities to maximize tourism potential. By investing in skills development and community engagement, Pulo Geulis can capitalize on its cultural richness and promote sustainable tourism development.